Question 8 Prove that [ cos (π+x) . cos (-x) ] / [ sin (π - x) . cos (π/2 +x) ] = (cot (x))^2
Class X1 - Maths -Trigonometric Functions Page 73
Answers
Answered by
268
LHS = {cos(π+x).cos(-x)}/{sin(π-x).cos(π/2-x)}
we know,
cos(π+x) = -cosx
sin(π-x) = sinx
cos(-x) = cosx
cos(π/2 + x) = -sinx, use this above .
LHS = {(-cosx).cosx}/{sinx.(-sinx}
= cos²x/sin²x
= cot²x = RHS
Answered by
88
Answer and explanation:
To prove :
Proof :
Applying trigonometric properties,
Substitute all the values in the expression,
Hence proved.
Similar questions
Math,
9 months ago
Social Sciences,
9 months ago
Math,
1 year ago
Math,
1 year ago
Social Sciences,
1 year ago
English,
1 year ago